GAMBARAN KONDISI KANTIN SEKOLAH PADA SEKOLAH DASAR DI WILAYAH KECAMATAN TEMBALANG KOTA SEMARANG - Laelatul Hikmah; Syamsulhuda BM; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Snacks of students in Tembalang sub-districtstill have 82.2% of bacteriological value and 37.8% of Salmonella sp.As many as 63,46% of school canteens condition in Tembalang sub-district had poor sanitation quality and 76,92% of food storage area wasn’t protected from pollutant sources.The objective of this research was described elementary school canteen condition in Tembalang sub-district. This research is a quantitative descriptive research with cross sectional design. Sampling in this study used the total population of schools having a canteen as many as 32 respondents.Methods of data collection through interviews using a questionnaire.The results showed that the condition of school canteen at elementary school in Tembalang sub-district was 84.4% less good.Based on the result of the research,it is found that the inputs in the school cafeteria including the infrastructure are 50% less good,the human resources 50% less good, 65,5% less good in fund, and 59,4% for Standard Operational Procedure (SOP) wasn’t good too. Infrastructure arrangement process was 50% less good,school canteen management 50% was less good,and food management was 56,3% less good. As many as 40,6% of students still buy snacks at traders outside the school. As for the regulation to not buy snacks outside of the school is only 62,5% of schools that already have that regulation and only 21,9% of schools that have sanctions related to the regulation.In the school canteen implementation needs to optimize the school canteen organizational structure,the existence of guidance in the implementation of school canteens and raising awareness of students and traders of healthy snacks.